UPCRISPR: an ultrafast, one-tube multiplexed nucleic acid detection system for resolving the diagnostic gray zone in HPV16/18 detection - Linlin Bai; Dianwei Liu; Chunyan Qian; Weiqi Yuan; Kaiming Guo; Yao Wang; Feng Qian; Mingmin Shi; Bei Wang; Rui Wang (Analytica Chimica Acta, 2026)

Fungal necromass dominates soil organic carbon accrual after decadal active restoration of alpine grassland - Shijie Zhou; Jinchao Gong; Keqi Fan; Abraham Allan Degen; Jingjing Wu; Xiongkui Lin; Tahmina Kausar; Yue Xiu; Linlin Li; Liang Tie; Ziwei Yang; Congyu Ma; et al. (Journal of Environmental Management, 2026)

Ecoenzymatic stoichiometry reveals higher microbial nitrogen limitation in active than passive restored alpine wetlands - Tahmina Kausar; Jingjing Wu; Saraj Bahadur; Abraham Allan Degen; Akash Tariq; Feida Sun; Jinchao Gong; Shijie Zhou; Yue Xiu; Linlin Li; Liang Tie; Jordi Sardans; et al. (Journal of Environmental Management, 2026)

Sustained Swimming Training Enhances Growth and Swimming Performance in Juvenile Coho Salmon (Oncorhynchus kisutch) with Limited Effects on Osmoregulatory-Related Traits - Wenda Cui; Hexiang Yang; Shuang Song; Linlin Dai; Hongyang Chen; Junjie Bai; Binbin Xing; Xintong Qiu (Fishes, 2026)
To evaluate the effects of swimming training on growth, swimming performance, and osmoregulatory-related indices in juvenile coho salmon, freshwater-reared fish were subjected to current of 1 body length per second (BL·s−1) from December 2024 to April 2025. Fork length, body weight, condition factor, insulin-like growth factor-1 (IGF-1), and gill and intestinal Na+/K+-ATPase (NKA) protein abundance were measured monthly, and critical swimming speed (Ucrit) was evaluated after one month of training. Trained fish showed greater fork length in March and higher body weight in March and April than controls. The condition factor was higher in trained fish in February and March, but declined during spring smolt development. Swimming capacity was enhanced by training, as indicated by significantly higher Ucrit. Mean IGF-1 levels did not differ between groups, but IGF-1 correlated positively with body size only in trained fish. No significant training effect was detected for either gill or intestinal NKA protein abundance, although gill NKA increased significantly in April, likely reflecting seasonal smoltification. In addition, IGF-1 was significantly correlated with gill NKA in trained fish in March. Collectively, these results indicate that sustained swimming training improves growth and swimming performance and may enhance associations among measured physiological variables during smoltification in juvenile coho salmon.

Effects of combined selenium and sulfur application on glucosinolate biosynthesis in Chinese cabbage sprouts - Huixia Bai; Linlin Zhao; Yafang Luo; Qi Hu; Lingling Liu; Yang Chen; Huan Wang; Yushu Wang (Physiology and Molecular Biology of Plants, 2026)

Unlocking the anatomical code of flavor and lipids in grass carp (Ctenopharyngodon idellus) fish oil from different tissue parts by SPME-GC–MS, molecular docking, and lipidomics - Huijuan Zhou; Linchuan Xu; Junru Bai; Linlin Weng; Chengwei Yu; Mingming Hu; Bizhen Zhong; Jinlin Li; Zongcai Tu; Bin Peng (Food Chemistry, 2026)

Holocene wildfire activity archived in East Asian marginal sea: Linkages to climate variability and human civilization - Linlin Chen; Yazhi Bai; Zhigang Guo; Weini Chong; Yuying Zhang; Jinming Bai; Yaru Liu; Haiyan Fang; Limin Hu (CATENA, 2026)

Meso–Neoproterozoic rift system along the southwestern North China Craton: evidence from recent drilling and seismic data - Zhenhong Li; Xiaopeng Dong; Haifeng Bai; Yijun Zhou; Jiawei Cui; Linlin Kou; Fang Wu (International Geology Review, 2026)

Bone mesenchymal stem cells attenuate axonopathy in spinal cord of rats exposed to 2,5-hexanedione via NGF-dependent and -independent pathways - Qiufang Bai; Zhe Li; Jing Chen; Man Liu; Xiaodan Shao; Xiaochi Chen; Fengyuan Piao; Linlin Fang (Molecular and Cellular Biochemistry, 2026)

Carbonized polymer dots as drivers of modernization in Chinese Herbal Medicine - Linlin Zhang; Ying Cheng; Xin Yang; Xiaoyu Chang; Siyu Lu; Bai Yang; Xiaoli Qu (Science Bulletin, 2026)

Bioorthogonally activatable methylene blue platform for selective prodrug activation and fluorescent imaging in living systems - Linlin Yang; Shiqiong Bai; Yuqing Nie; Yixuan Li; Fei Xin; Panpan Song; Na Gao; Liguo Ji; Lili Li; Guangjie He (Analytica Chimica Acta, 2026)

Preparation of a Near-infrared Probe Based on Triphenylamine Thiophene and its Use for the Fluorescence Imaging of H2S in Living Cells - Lu Yang; Huan Li; Miaomiao Li; Aoxiang Fu; Shiqiong Bai; Jing Li; Linlin Yang; Guangjie He (Journal of Fluorescence, 2025)

CUR-PDT induces ferroptosis of RA-FLS via the Nrf2/xCT/GPX4 pathway to inhibit proliferation in rheumatoid arthritis - Lihua Sun; Yajuan Niu; Bo Liao; Linlin Liu; Yi Peng; Kaiting Li; Xinhua Chen; Qing Chen; Dingqun Bai (Inflammation Research, 2025)

SIMPLE: A One-Pot RPA-Cas12b Method for Single Nucleotide Variations Identification with an Expanded Scope and Clinical Applications - Kaiming Guo; Yongkang Lai; Yiru Han; Linlin Bai; Ting Wang; Shengzhou Wang; Ziqin Zhang; Dianwei Liu; Yanju Chen; Jiulong Zhao; Yanan Pang; Feng Qian; et al. (Phenomics, 2025)

Occupational exposure to amorphous silica nanoparticles alters lung function and metabolomic features - Xuemin Shi; Chen Liang; LinLin Wang; Xuefeng Bai; Ruiyang Ding; Zhiwei Sun (Toxicology Letters, 2025)

Graphite-catalyzed carbonization of biowaste unlocks energy-dense, high-rate, and long-lifespan potassium-ion batteries - Jiale Chen; Lulu Tan; Chengye Lin; Yue Bai; Xiaogang Niu; Zhe Zhang; Nan Li; Linlin Wang; Ye Wang; Xiao Ji; Yujie Zhu (Chemical Engineering Journal, 2025)

Distribution of glucosinolates and antioxidants in different leaf-layers of Kale (Brassica oleracea var. acephala DC.) - Yafang Luo; Huixia Bai; Linlin Zhao; Qi Hu; Xinyuan Li; Zhenyu Fan; Yushu Wang (Physiology and Molecular Biology of Plants, 2025)

MVPCR: Multiplex Visual Detection Strategy Based on Ultrafast PCR for Point-of-Care Pathogens Detection Within 10 Min - Ziqin Zhang; Cui Wu; Linlin Bai; Kaiming Guo; Ting Wang; Dianwei Liu; Mingrui Zhu; Feng Qian; Fang Zhang; Rui Wang (Phenomics, 2025)

Research on real-time monitoring and early warning of Tangshan road surface subsidence based on InSAR - Mingzhou Bai; Yanli Qi; Linlin Song; Qihao Wang; Zilun Zhang; Gang Tian (Advances in Space Research, 2025)

Effect of Feeding Mice Soluble Metals and Heavy Metal Contaminated Soil on Feces Metal Concentrations - Ningning Xu; Liping Li; James A. Ippolito; Weiqin Xing; Yale Wang; Baozhong Zhang; Yongqiang Yang; Ling Bai; Linlin Zhao (Biological Trace Element Research, 2025)

Plant extracellular vesicles contribute to the amplification of immune signals during systemic acquired resistance - Wenjing Wang; Junsong Zhang; Liying Pan; Zijia Liu; Weiwei Yi; Xiaolong Xing; Linlin Bai; Qiao Liu; Qingbin Chen; Lingyu Mi; Qingfeng Zhou; Dongli Pei; et al. (Plant Cell Reports, 2025)

Comparative analysis of climate-induced habitat shift of economically significant species with diverse ecological preferences in the Northwest Pacific - Wanchuan Dong; Xinlu Bai; Linlin Zhao; Hao Dong; Changdong Liu (Frontiers in Marine Science, 2024)
The Northwest Pacific Ocean is the most productive fishing ground in the Pacific Ocean, with a continuous rise in water temperature since 1990. We developed stacked species distribution models (SSDMs) to estimate the impacts of climate change on the distribution dynamics of economically significant species under three climate change scenarios for the periods 2040-2060 and 2080-2100. Overall, water temperature is the most important factor in shaping the distribution patterns of species, followed by water depth. The predictive results indicate that all the species show a northward migration in the future, and the migration distance varies greatly among species. Most pelagic species will expand their habitats under climate change, implying their stronger adaptability than benthic species. Tropical fishes are more adaptable to climate change than species in other climate zones. Though limitations existed, our study provided baseline information for designing a climate-adaptive, dynamic fishery management strategy for maintaining sustainable fisheries.

Effect of sodium selenite on the synthesis of glucosinolates and antioxidant capacity in Chinese cabbage (Brassica rapa L.ssp.pekinensis) - Yafang Luo; Shuang Zhao; Huan Wang; Huixia Bai; Qi Hu; Linlin Zhao; Tianyi Ma; Zhenyu Fan; Yushu Wang (Physiology and Molecular Biology of Plants, 2024)

A robust transformer-based pipeline of 3D cell alignment, denoise and instance segmentation on electron microscopy sequence images - Jiazheng Liu; Yafeng Zheng; Limei Lin; Jingyue Guo; Yanan Lv; Jingbin Yuan; Hao Zhai; Xi Chen; Lijun Shen; LinLin Li; Shunong Bai; Hua Han (Journal of Plant Physiology, 2024)

Polycyclic aromatic hydrocarbons exposure and arterial stiffness-related plasma miRNAs: A panel study - Ziqian Zhang; Conghua Bai; Lei Zhao; Linlin Liu; Wenting Guo; Miao Liu; Huihua Yang; Xuefeng Lai; Xiaomin Zhang; Liangle Yang (Environmental Toxicology and Pharmacology, 2024)

Bioaerosols in deodorization covers of wastewater treatment plants: Emission characteristics and health risks - Shan Zhao; Yang Liu; Jiang Chang; Jiawei Wang; Hao Peng; Baocong Cui; Jin Bai; Yanjie Wang; Linlin Hua (Chemosphere, 2024)

Extracellular vesicles in plant-microbe interactions: Recent advances and future directions - Junsong Zhang; Liying Pan; Wenjie Xu; Hongchao Yang; Fuge He; Jianfeng Ma; Linlin Bai; Qingchen Zhang; Qingfeng Zhou; Hang Gao (Plant Science, 2024)

Ginsenoside Rk1 induces autophagy-dependent apoptosis in hepatocellular carcinoma by AMPK/mTOR signaling pathway - Huanyan Wu; Linlin Qu; Xue Bai; Chenhui Zhu; Yuan Liu; Zhiguang Duan; Hongyan Liu; Rongzhan Fu; Daidi Fan (Food and Chemical Toxicology, 2024)

A prospective comparative study on bladder volume measurement with portable ultrasound scanner and CT simulator in pelvic tumor radiotherapy - Fei Bai; Qiuxia Hu; Xiaowei Yao; Ming Cheng; Lina Zhao; Linlin Xu (Physical and Engineering Sciences in Medicine, 2024)
Objective: The consistency of bladder volume is very important in pelvic tumor radiotherapy, and portable bladder scanner is a promising device to measure bladder volume. The purpose of this study was to investigate whether the bladder volume of patients with pelvic tumor treated with radiotherapy can be accurately measured using the Meike Palm Bladder Scanner PBSV3.2 manufactured in China and the accuracy of its measurement under different influencing factors. Methods: A total of 165 patients with pelvic tumor undergoing radiotherapy were prospectively collected. The bladder volume was measured with PBSV3.2 before simulated localization. CT simulated localization was performed when the bladder volume was 200-400ml. The bladder volume was measured with PBSV3.2 immediately after localization and recorded. The bladder volume was then delineated on CT simulation images and recorded. To compare the consistency of CT simulation bladder volume and bladder volume measured by PBSV3.2. To investigate the accuracy of PBSV3.2 in different sex, age, treatment purpose, and bladder volume. Results: There was a significant positive correlation with bladder volume on CT and PBSV3.2 ( r = 0.874; p < 0.001). The mean difference between CT measured values and PBSV3.2 was (-0.14 ± 50.17) ml. The results of the different variables showed that the overall mean of PBSV3.2 and CT measurements were statistically different in the age ≥ 65 years, bladder volumes > 400ml and ≤ 400ml groups ( p = 0.028, 0.002, 0.001). There was no statistical significance between the remaining variables. The volume difference between PBSV3.2 measurement and CT was 12.87ml in male patients, which was larger than that in female patients 3.27ml. Pearson correlation analysis showed that the correlation coefficient was 0.473 for bladder volume greater than 400ml and 0.868 for bladder volume less than 400ml; the correlation coefficient of the other variables ranged from 0.802 to 0.893. Conclusion: This is the first large-sample study to evaluate the accuracy of PBSV3.2 in a pelvic tumor radiotherapy population using the convenient bladder scanner PBSV3.2 made in China. PBSV3.2 provides an acceptable indicator for monitoring bladder volume in patients with pelvic radiotherapy. It is recommended to monitor bladder volume with PBSV3.2 when the planned bladder volume is 200-400ml. For male and patients ≥ 65 years old, at least two repeat measurements are required when using a bladder scanner and the volume should be corrected by using a modified feature to improve bladder volume consistency.

Sulfur-Doped porous carbon Adsorbent: A promising solution for effective and selective CO2 capture - Jiali Bai; Jiawei Shao; Qiyun Yu; Muslum Demir; Bilge Nazli Altay; Turgunov Muhammad Ali; Yongfu Jiang; Linlin Wang; Xin Hu (Chemical Engineering Journal, 2024)

Paleoproterozoic skarn mineralization events and geodynamic background in the Jiao-Liao-Ji Belt: Geological, geochemical and chronological evidence from the Daqinggou Fe–Cu polymetallic deposit in Ji'an, NE China - YanPeng Liu; JingGui Sun; LinLin Wang; ZhiKai Xu; ChengLin Bai; Xiang Chang; TingTing Zhang (Precambrian Research, 2023)

Dualistic cascade convolutional neural network dedicated to fully PolSAR image ship detection - Gui Gao; Qilin Bai; Chuan Zhang; Linlin Zhang; Libo Yao (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Nitrogen-doped porous carbons from polyacrylonitrile fiber as effective CO2 adsorbents - Changdan Ma; Jiali Bai; Xin Hu; Zhuohan Jiang; Linlin Wang (Journal of Environmental Sciences, 2023)

Study on construction deformation prediction and disaster warning of karst slopes based on grey theory - Yanli Qi; Gang Tian; Mingzhou Bai; Linlin Song (Bulletin of Engineering Geology and the Environment, 2023)

Operation performance of an ultralow-temperature cascade refrigeration freezer with environmentally friendly refrigerants R290-R170 - Haihui Tan; Lingfei Xu; Linlin Yang; Minkai Bai; Zhan Liu (Environmental Science and Pollution Research, 2022)

Genome-wide association study of grain shapes in Aegilops tauschii - Xinpeng Zhao; Linlin Lv; Jiahui Li; Feifei Ma; Shenglong Bai; Yun Zhou; Dale Zhang; Suoping Li; Chun-peng Song (Euphytica, 2021)

Physiological responses of yellow-horn seedlings to high temperatures under drought condition - Hua Jin; Jixiang Zou; Linlin Li; Xinlei Bai; Tong Zhu; Junbao Li; Bingcheng Xu; Zhi Wang (Plant Biotechnology Reports, 2020)

The role of Ustilaginoidea virens sclerotia in increasing incidence of rice false smut disease in the subtropical zone in China - Mingli Yong; Qide Deng; Linlin Fan; Jiankun Miao; Chaohui Lai; Hongming Chen; Xiujuan Yang; Shu Wang; Furu Chen; Li Jin; Binghui Yang; Yuanjun Bai; et al. (European Journal of Plant Pathology, 2018)

miR-155 promotes cutaneous wound healing through enhanced keratinocytes migration by MMP-2 - Longlong Yang; Zhao Zheng; Qin Zhou; Xiaozhi Bai; Lei Fan; Chen Yang; Linlin Su; Dahai Hu (Journal of Molecular Histology, 2017)

Allogeneic adipose-derived stem cells promote survival of fat grafts in immunocompetent diabetic rats - Jun Zhang; Xiaozhi Bai; Bin Zhao; Yunchuan Wang; Linlin Su; Peng Chang; Xujie Wang; Shichao Han; Jianxin Gao; Xiaolong Hu; Dahai Hu; Xiaoyan Liu (Cell and Tissue Research, 2016)

Role of Exogenous Nitric Oxide in Alleviating Iron Deficiency Stress of Peanut Seedlings (Arachis hypogaea L.) - Jing Kong; Yuanjie Dong; Yiling Song; Xiaoying Bai; Xianyi Tian; Linlin Xu; Shuang Liu; Zhenli He (Journal of Plant Growth Regulation, 2016)

Event-related potentials elicited by social commerce and electronic-commerce reviews - Yan Bai; Zhong Yao; Fengyu Cong; Linlin Zhang (Cognitive Neurodynamics, 2015)

Effects of Exogenous Salicylic Acid on Alleviating Chlorosis Induced by Iron Deficiency in Peanut Seedlings (Arachis hypogaea L.) - Jing Kong; Yuanjie Dong; Linlin Xu; Shuang Liu; Xiaoying Bai (Journal of Plant Growth Regulation, 2014)

Growth inhibition induced by transforming growth factor-β1 in human oral squamous cell carcinoma - Xiumei Wang; Wenjing Sun; Jing Bai; Linlin Ma; Yang Yu; Jingshu Geng; Jiping Qi; Zhongcheng Shi; Songbin Fu (Molecular Biology Reports, 2009)